CREATIVE AND ORGANIZATIONAL MODEL OF PROFESSIONAL TRAINING OF A FUTURE PRIMARY TEACHER - Gulmira Rifovna Tojiboeva; Kamila Khojamberdieva; Luiza Berdieva (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the problems of preparing a future primary school teacher based on a creative organizational model. Positive trends in the development of modern primary education in the Republic of Uzbekistan are revealed.